PEMERIKSAAN KADAR ASAM MERKAPTOASETAT DALAM SEDIAAN PENGERITING RAMBUT YANG BEREDAR DI SALON SEKITAR UNIVERSITAS SARI MUTIARA INDONESIA - Siti Nurbaya; Siti Maimunah; Kesaktian Manurung; Risda Hernidawati Nainggolan (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Cosmetics used for this purpose, such as curling hair, use hair curling preparations containing mercaptoacetic acid. Curling hair aims to change the structure of straight hair into wavy. The purpose of this study was to determine the levels of mercaptoacetic acid in hair curling preparations circulating in salons around Sari Mutiara University, Indonesia. The research was conducted on 3 types of samples determined by iodometric titration method using potassium iodide titer solution and starch indicator. The results of this study examined the levels of mercaptoacetic acid in hair curling preparations in samples A: 5,676%, B: 6,053%, C: 6,478%. These results indicate that the 3 types of samples meet the requirements in accordance with the decision of the POM RI No. HK.00.05.42.1018 the Year 2008 with a maximum level of 8.0%.